Jual Beli Online Dalam Perspektif Ekonomi Islam Pada Mahasiswa FEBI UNZAH - Zahida I’tisoma Billah; Wahyu Nuril Khotimah (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this study is to find out how the practice of buying and selling online conducted by students of the Faculty of Islamic economics and business at UNZAH and to find out the practice of buying and selling online in an Islamic perspective. The research method used in this study is descriptive qualitative method with Case Study approach. The data sources used are primary data and secondary data with data collection techniques in the form of observation, interviews, and documentation. Data analysis method in this study by reducing the data, after that present the data and draw conclusions of the data. The results showed that the practice of online buying and selling carried out by unzah students occurred in the first two ways the transaction mechanism which means the first step of the buyer to order goods and after that there is an online payment transaction also with several payment systems, among others by using bank transfer, credit card, paypal, e-wallet and can also be with the COD system. Online buying and selling carried out by online sellers Islamic Economic Perspective is in accordance with the transaction according to Islamic law, among others, the product/item sold must also be halal and quality, clarity of the status of the item is personal property or person, second hand and quality as well. Price compliance with the quality of the goods must also be guaranteed so that buyers do not feel disappointed. Honesty in buying and selling online should also be applied especially issues related to the level of trust between both parties.